By grammar alone? Humanism overcome and the hermeneutics of Matthias Flacius Illyricus - Koryl, Jakub (2020)
Wilhelm Dilthey once admitted that Matthias Flacius Illyricus either appropriated the fourth book of Augustine’s De Doctrina Christiana in detail or took advantage of all of the early Christian exegesis in general in his Clavis Sacrae Scripturae. The aim of this paper is partly polemical. While Flacius himself frequently proved Dilthey’s unfavorable judgment to be correct, he also followed the innovatory footsteps of biblical philologists such as Gianozzo Manetti, Lorenzo Valla and Desiderius Erasmus in order to reaffirm and concretize the Lutheran principle of the intelligibility of Scripture based on its strictly immanent, that is to say grammatical, investigation. Consequently, I would like to discuss the Clavis Sacrae Scripturae as the confessional yet deliberate outcome of the grammatical and rhetorical curriculum of studia humanitatis. All of this, however, will not lead to the conclusion that the Clavis should still remain the enterprise of a less distinguished follower. For decisions made by Flacius regarding the tradition of patristic, medieval, and humanistic exegesis was constantly founded upon the heuristically critical and genuinely hermeneutical principle. Therefore, it is worth asking what this principle was, or more precisely, how can man use philological tools that do not deprive God of his unconditioned sovereignty.
Jednom je Wilhelm Dilthey ocijenio da je Matija Vlačić Ilirik u svojoj Clavis Sacrae Scripturae ili u potpunosti usvojio Augustinovu De Doctrina Christiana ili pak iskoristio sve ranije kršćanske egzegeze općenito. Cilj je ovoga rada dijelom polemičke naravi: s jedne strane Vlačić često potvrđuje istinitost te Diltheyeve po njega nepovoljne tvrdnje, dok s druge strane kroči inovativnim stopama biblijskih filologa (Gianozzo Manetti, Lorenzo Valla i Desiderius Erasmus) nastojeći reafirmirati i konkretizirati luteranski princip razumijevanja Svetog pisma na temelju strogo imanentnoga, dakle gramatičkoga, ispitivanja. Posljedično, u radu se propituje Clavis Sacrae Scripturae kao konfesionalni, ali istovremeno i slobodno promišljeni ishod gramatičkog i retoričkog kurikula studia humanitatis. To međutim ne vodi k zaključku da Clavis treba i dalje smatrati pothvatom manje cijenjenoga sljedbenika jer su neke Vlačićeve odluke u smislu patrističke tradicije, srednjovjekovne i humanističke egzegeze dosljedno utemeljene na heurističkoj kritici i istinskom hermeneutičkom principu. To čini legitimnim propitivanje o kojem je principu riječ, ili preciznije: na koji način čovjek može primjenjivati filološke alate koji Boga ne lišavaju njegove neprikosnovenosti?
Bibliografske bilješke uz tekst ; bibliografija: str. 254-255.
Summary ; Sažetak.
Keywords: Sola scriptura -- Hermeneutika -- Gramatika -- Tradicija; Vlačić Ilirik, Matija